Determination of carbofuran in water samples from pay-fishing farms in itumbiara – go and its health implications (Revista Brasileira Multidisciplinar, 2026)
In Brazil, the intensive use of pesticides has intensified since the 1970s, with government incentives, with carbofuran being one of the most widely used compounds in agriculture. Despite its ban in 2017 by the National Health Surveillance Agency (ANVISA), due to its high toxicity, its residues still pose a risk to public health, and can cause neurological and endocrine disorders. This study aimed to determine the presence of carbofuran residues in water samples collected from fishing establishments located in the municipality of Itumbiara, Goiás, Brazil. Analyses were performed on samples obtained from three different points in each location, using the Liquid-Liquid Extraction with Low Temperature Partitioning (LLE-LTP) technique and analysis by High Performance Liquid Chromatography with Ultraviolet detector (HPLC-UV). The water samples did not present carbofuran residues under the analytical conditions applied, or were below the detection limit. The study reinforces the importance of continuous monitoring of pesticide residues in aquatic environments, especially in regions with a history of agricultural use, as an essential public health surveillance measure.
Keywords: Pesticides; Pay-fishing; Toxicity; Water contamination; Public health